2017
DOI: 10.26831/bssj.2016.2.1.113-133
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Customer Repurchase Intention in the Fast Food Industry. A Case Study of Innscor Mutare, Zimbabwe

Abstract: This research is focused on finding the factors that influence customer repurchase intentions in the fast food industry. Fast food concepts have developed very rapidly in last few years in Zimbabwe. The failure or success of a fast food industry is based on some factors like Promotion, Service quality, Customer expectations, Brand, Physical Environment, Price, and Taste of the product. To find which of these factors has a greater influence on consumer retention, four fast food restaurants were targeted randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
(11 reference statements)
0
3
0
1
Order By: Relevance
“…They typically base future purchase intentions on the value gained from earlier contacts, with relationship benefits serving as a surrogate for future advantage expectations. Repurchase intention is typically determined by surveys of current consumers, which examine their proclivity to buy the same brand, product/service and from the same company (Fungai, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They typically base future purchase intentions on the value gained from earlier contacts, with relationship benefits serving as a surrogate for future advantage expectations. Repurchase intention is typically determined by surveys of current consumers, which examine their proclivity to buy the same brand, product/service and from the same company (Fungai, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of their studies revealed that food quality attributes such as taste, appearance and temperature significantly affect customer satisfaction and selection of restaurant. The findings of Hyun (2010) corraborates Fungai (2017), Qu (2018) and Mohammad (2019) studies who found that quality of food greatly influence consumers' choice of eatery.…”
Section: Factorsmentioning
confidence: 90%
“…The cuisine is therefore the most important factor in having the ideal dining experience (Fungai, M. (2017). [183]). Menu: One of the crucial factors that have to be taken into consideration while assessing menu performances is the quantity of plate waste.…”
Section: Quality Of Foodmentioning
confidence: 99%